2020
DOI: 10.1167/tvst.9.10.29
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Repeatability of High Resolution and High Speed Scans from Spectralis Optical Coherence Tomography Angiography

Abstract: The purpose of this study was to evaluate and compare the repeatability of optical coherence tomography angiography (OCTA) derived retinal vascular quantitative metrics using high resolution (HR) versus high speed (HS) acquisition modes. Methods: Macular 4.4 × 2.9-mm OCTA images from normal, healthy volunteers were captured using both HR (768 A-scans × 256 B-scans) and HS (384 A-scans × 256 B-scans) acquisition protocols. Vessel density and vessel length density of the superficial capillary plexus and deep cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…To mitigate these changes, several devices contain projection removal functions which remove the flow signal cast by overlying retinal vessels from the choriocapillaris slab. Many image processing strategies independent of the OCTA devices have also been adopted to eliminate these potentially confounding residual shadow or projection artifacts [ 9 , 24 , 25 , 26 , 27 , 28 ]. Motion artifacts created by body and eye movement and reduced signal strength of the images can also profoundly reduce the accuracy of quantitative analysis of the choriocapillaris [ 1 , 29 ].…”
Section: Octa Analysis Of the Choriocapillarismentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate these changes, several devices contain projection removal functions which remove the flow signal cast by overlying retinal vessels from the choriocapillaris slab. Many image processing strategies independent of the OCTA devices have also been adopted to eliminate these potentially confounding residual shadow or projection artifacts [ 9 , 24 , 25 , 26 , 27 , 28 ]. Motion artifacts created by body and eye movement and reduced signal strength of the images can also profoundly reduce the accuracy of quantitative analysis of the choriocapillaris [ 1 , 29 ].…”
Section: Octa Analysis Of the Choriocapillarismentioning
confidence: 99%
“…The limitations of this method include the lack of a globally approved and validated normal database and the use of one standard deviation as a threshold, which is debated. Currently, the most commonly used approach is the Phansalkar local thresholding method [ 1 , 10 , 12 , 26 , 27 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. This method sets a circle with a certain “Phansalkar radius” around each pixel, and creates a threshold based off of the intensity mean and standard deviation inside the circle.…”
Section: Octa Analysis Of the Choriocapillarismentioning
confidence: 99%
“…These results suggested that reduction in blood flow and impairment of the blood–retinal barrier have occurred because of chronic hyperglycemia before apparent signal of DR in children with T1DM. As a noninvasive and repeatable technique, 18 OCTA is an available technology to detect and closely follow-up the earlier microvascular changes of retina in children with T1DM without clinical DR. In future, VD of retina may be an important indicator to predict and monitor the T1DM DR in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a moderate agreement between CVIs obtained from scans acquired using a different pupil entry position of the beam and suggested to always use the same direction of the beam to standardize CVI measurements [ 20 ]. Corvi et al, analyzed the repeatability of OCT angiography derived retinal quantitative metrics using HR versus HS acquisition modes, reporting statistically significant different values [ 21 ].…”
Section: Discussionmentioning
confidence: 99%